Noise and Infrasonic Noise at Workplaces in a Wind Farm - PLEBAN, Dariusz; RADOSZ, Jan; SMAGOWSKA, Bożena (Archives of Acoustics, 2017)
Dynamic development of wind power should take into account requirements resulting from environmental protection and human health. However in the case of occupational exposure to noise emitted by wind turbines (workplaces of wind turbine operation personnel, including persons performing maintenance) there are no documented data in literature in this regard. An example of pilot assessments of noise and infrasonic noise at workplaces in a wind farm is presented in the paper. The results of measurements and assessments of noise emitted by the wind turbines Vestas V80-2.0 MW show that noise does not constitute health hazard for wind farm workers. Furthermore infrasonic noise emitted by the wind turbines Vestas V80-2.0 MW is not an annoyance agent for wind farm workers.